Energy-Aware Routing Protocol for Ad Hoc Wireless Sensor Networks - Mann Raminder P; Namuduri Kamesh R; Pendse Ravi (EURASIP Journal on Wireless Communications and Networking, 2005)
Wireless ad hoc sensor networks differ from wireless ad hoc networks from the following perspectives: low energy, lightweight routing protocols, and adaptive communication patterns. This paper proposes an energy-aware routing protocol (EARP) suitable for ad hoc wireless sensor networks and presents an analysis for its energy consumption in various phases of route discovery and maintenance. Based on the energy consumption associated with route request processing, EARP advocates the minimization of route requests by allocating dynamic route expiry times. This paper introduces a unique mechanism for estimation of route expiry time based on the probability of route validity, which is a function of time, number of hops, and mobility parameters. In contrast to AODV, EARP reduces the repeated flooding of route requests by maintaining valid routes for longer durations.